A mmWave Phase Shifter Based on Ferroelectric Hafnium Zirconium Oxide Varactors - Sukhrob Abdulazhanov; Quang Huy Le; Dang Khoa Huynh; Defu Wang; Gerald Gerlach; Thomas Kämpf (2019 IEEE MTT-S International Microwave Workshop Series on Advanced Materials and Processes for RF and THz Applications (IMWS-AMP), 2019)
This paper presents a 60 GHz phase shifter, based on a coplanar waveguide (CPW) transmission line, loaded with ferroelectric hafnium zirconium oxide (HZO) variable metal-insulator-metal (MIM) varactors, developed for the back-end-of-line (BEoL) on-chip integration. Using the measured data of capacitance-voltage (C-V) characteristics of HZO and implementing the method-of-moments simulation, it was shown, that by changing the bias voltage between 0.95 and -3 V, the device shows a phase shift of 111° and a minimum insertion loss of -5.84 dB at 60 GHz. The chip area of the device is 0.206 mm 2 , making it the smallest among non-CMOS phase shifters.